Hubungan Perilaku Merokok Keluarga dengan Bronkopneumonia pada Balita di RS Sari Asih Ciledug - Iin Indriani; Hernandia Distinarista; Tutik Rahayu (Journal of Health, Medical, and Psychological Studies, 2026)
Bronchopneumonia is one of the leading causes of morbidity among children under five years of age and remains a common health problem. Exposure to cigarette smoke inside the household due to the smoking behavior of family members is an important environmental risk factor. Toddlers have immature immune systems and lung function, making them more susceptible to the adverse effects of cigarette smoke. This study aimed to determine the relationship between family members’ smoking behavior and the incidence of bronchopneumonia among children under five at Sari Asih Ciledug Hospital. This study employed a quantitative research design with a cross-sectional approach. The sample consisted of 83 respondents selected using a total sampling technique. Data on family members’ smoking behavior were collected through a structured questionnaire, while data on the incidence of bronchopneumonia in toddlers were obtained from hospital medical records. Data analysis was performed using univariate analysis to describe respondent characteristics and bivariate analysis using the Chi-Square test to examine the relationship between variables. The results showed a statistically significant relationship between family members’ smoking behavior and the incidence of bronchopneumonia among toddlers (p < 0.05). The Prevalence Odds Ratio (POR) value of 16.640 indicated that toddlers exposed to cigarette smoke had a higher risk of developing bronchopneumonia compared to those who were not exposed